Peningkatan Kapasitas Petani Sawit Melalui Penerapan Standar RSPO di KMD Talang Petai, Kabupaten Mukomuko: Penelitian - Hamdani; Tuty Ningsih; Eka Boby Febrianto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The implementation of the Roundtable on Sustainable Palm Oil (RSPO) standard is a strategic step in enhancing the competitiveness and sustainability of Indonesia’s smallholder palm oil sector. This community engagement program aims to strengthen the capacity of palm oil farmers in the Talang Petai Village Community Cooperative (KMD Talang Petai), Mukomuko Regency—under the guidance of PT Agro Muko—in understanding and applying RSPO principles and criteria. The activities were carried out through training sessions, awareness campaigns, and institutional mentoring. The results show a significant improvement in farmers’ understanding of sustainability concepts, increasing from 42% to 85%, the adoption of Good Agricultural Practices (GAP), and the establishment of a cooperative Internal Control System (ICS) as an RSPO certification.The collaborative approach involving academia, the private sector, and the community has proven effective in strengthening smallholder readiness for sustainable palm oil production.